FORMATION OF SUPERCONDUCTING (TI,BI)SR2CACU2OY THIN-FILMS BY RF-SPUTTERING AND THALLIUM DIFFUSION - Liu, R; Edwards, P; Hunneyball, P; Bennett, M; Jedamzik, D; Harrison, M; Horley, R (1990)
We have prepared new high Tc superconducting thin films of (Tl,Bi)-Sr-Ca-Cu-O by combining low temperature (500 °C) rf sputtering of Bi-Sr-Ca-Cu-O precursor films and thallium diffusion. A typical film has T c(onset) =80 K, Tc(midpoint) =79 K, and T c(zero) =50 K. X-ray diffraction and energy dispersive spectroscopic studies were carried out to determine the composition and crystal structure of the superconducting phase within the film. We identified a material with the chemical composition of (Tl0.7 Bi0.3) Sr 2CaCu2Oy and tetragonal symmetry (a=3.795 Å and c=12.095 Å), and propose that this phase is responsible for superconductivity around 80 K. The film also has a highly preferred orientation with the c axis perpendicular to the surface of the (100)MgO substrate.